2015
DOI: 10.11113/sh.v8n1.697
|View full text |Cite
|
Sign up to set email alerts
|

Kebaikan Pekerjaan Keusahawanan Sebagai Pengantara Antara Faktor-Faktor Peramal dan Kecenderungan Pelajar Menceburi Kerjaya Keusahawanan

Abstract: Terengganu State Government set a vision to make "Terengganu a Fully Developed State by Year 2020." Expectations are amortized through the implementation of programs and public projects in line with the Ninth Malaysia Plan (2006) and Tenth (2011-2015. State Economic Development Corporation (SEDC) is an agency of the state government have a role and responsibility to help and provide a platform for students to apply the knowledge of entrepreneurship through direct involvement in secondary schools. Secondary sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Then the study will explore the effectiveness of entrepreneurship programs organized by universities in Malaysia toward the intention of students to become entrepreneurs in the future. This study continues previous studies in identifying entrepreneurial trends of youth and students, especially in the dimension of experiential activities and background of the university's program (Santoso & Oetomo, 2017;Shambare, 2013a;Toscher et al, 2020;Wan Nawang et al, 2015).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Then the study will explore the effectiveness of entrepreneurship programs organized by universities in Malaysia toward the intention of students to become entrepreneurs in the future. This study continues previous studies in identifying entrepreneurial trends of youth and students, especially in the dimension of experiential activities and background of the university's program (Santoso & Oetomo, 2017;Shambare, 2013a;Toscher et al, 2020;Wan Nawang et al, 2015).…”
Section: Introductionsupporting
confidence: 83%
“…Prior research has shown that entrepreneurship experiential activities can have a significant impact on students' entrepreneurial success (Nielsen & Gartner, 2017;Sharma & Madan, 2014;Wan Nawang et al, 2015). Students who participated in entrepreneurship competitions and incubator programs were more likely to start their businesses after graduation compared to those who did not participate.…”
Section: ) Entrepreneurship Experiential Activitiesmentioning
confidence: 99%
“…According to Mutalib (2013), student motivation towards entrepreneurship is the main factor in influencing students' tendencies to involve themselves in the field of entrepreneurship. In the study of Wan Nawang et al (2015), students have a moderate entrepreneurial personality because the motivation to achieve success and the willingness to take risks are not very positive. The motivation for using ICT is the tendency to use technology in the development of the digital era in the field of entrepreneurship (Omar & Ahmad Dimyati, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%